Peran Moderasi Usia dalam Pengaruh Nilai Konsumen terhadap Loyalitas Merek The Moderating Role of Age in the Effect of Consumer Value on Brand Loyalty - aji rahman purnama; aji rahman purnama (Universitas Veteran Bangun Nusantara, 2020)
ABSTRACTThe number of smartphone manufacturers offering the latest innovations has resulted in intense competition among smartphone manufacturers. This makes brand loyalty among smartphone users an interesting issue to research. On the other hand, in previous studies on the topic of brand loyalty, not many have conceptualized the moderating role of age. To answer these problems, this study aims to examine and analyze the moderating role of age in the influence relationship between perceived value and brand loyalty. The sample in this study were 100 smartphone users with the I phone brand in the Solo Raya area. The data collection method in this study used a questionnaire. Testing was carried out using Moderated Regression Analysis through IBM SPSS Statistic 23 software. The results of hypothesis testing in this study indicate that emotional value has a positive effect on brand loyalty, social value has a positive effect on brand loyalty, while functional value has a positive effect on brand loyalty. Age does not moderate the influence relationship between functional value, emotional value, and social value on brand loyalty. Keywords: brand loyalty, smartphone, perceived value